A structural model reveals energy transduction in dynein - Serohijos, Adrian W. R. (National Academy of Sciences, 2006)
Intracellular active transport is driven by ATP-hydrolyzing motor proteins that move along cytoskeletal filaments. In particular, the microtubule-associated dynein motor is involved in the transport of organelles and vesicles, the maintenance of the Golgi, and mitosis. However, unlike kinesin and myosin, the mechanism by which dynein converts chemical energy into mechanical force remains largely a mystery, due primarily to the lack of a high-resolution molecular structure. Using homology modeling and normal mode analysis, we propose a complete atomic structure and a mechanism for force generation by the motor protein dynein. In agreement with very recent electron microscopy (EM) reconstructions showing dynein as a ring-shaped heptamer, our model consists of six ATPases of the AAA (ATPases associated with various cellular activities) superfamily and a C-terminal domain, which is experimentally known to control motor function. Our model shows a coiled coil spanning the diameter of the motor that accounts for previously unidentified structures in EM studies and provides a potential mechanism for long-range communication between the AAA domains. Furthermore, normal mode analysis reveals that the subunits of the motor that contain the nucleotide binding sites exhibit minimal movement, whereas the rest of the motor is very mobile. Our analysis suggests the likely domain rearrangements of the motor unit that generate its power stroke. This study provides insights into the structure and function of dynein that can guide further experimental investigations into energy transduction in dynein.